An economic method for chitosan production - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
Chitosan is a deacetylated derivative of chitin, which is a naturally abundant mucopolysaccharide, supporting the matter of crustaceans, insects, and fungi. Because of its unique properties, such as non-toxicity, biodegradability, and biocompatibility, chitosan has a wide range of applications in various fields. Increasing interest on chitosan's usage has resulted in high consumption. Therefore, production of chitosan from essential sources with desired characteristics has become an important issue. Several methods, with different chemicals and reaction conditions, have been reported in the literature. This study aimed to shed light in several features of a very promising chitin isolation method described by Tolaimate et al. and its effect on the produced chitosan's phisico-chemical characteristics.
Keywords: chitosan; economic production; characterization